2006
DOI: 10.1093/carcin/bgl187
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA repair polymorphisms with DNA repair functional outcomes in healthy human subjects

Abstract: We investigated association between polymorphisms in DNA repair genes and the capacity to repair DNA damage induced by gamma-irradiation and by base oxidation in a healthy population. Irradiation-specific DNA repair rates were significantly decreased in individuals with XRCC1 Arg399Gln homozygous variant genotype (0.45 +/- 0.47 SSB/10(9) Da) than in those with wild-type genotype (1.10 +/- 0.70 SSB/10(9) Da, P=0.0006, Mann-Witney U-test). The capacity to repair oxidative DNA damage was significantly decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 27 publications
6
89
1
6
Order By: Relevance
“…It is widely accepted that alterations in XRCC1 may play important roles in the process associated with the etiology of cancers because of the alteration of base excision repair functions (Monaco et al, 2007). The functional significance of XRCC1 Arg194Trp polymorphism is due to the location in an evolutionarily conserved region, and the occurrence of chromosomal breaks is largely increased among cases with the Arg/Arg genotype (Vodicka et al, 2007). The Arg280His is located in the PCNA-binding region of XRCC1, and could potentially alter the structure DOI:http://dx.doi.org/10.7314/APJCP.2012.13.12.6385 XRCC1 Genetic Polymorphisms and Thyroid Carcinoma Risk: a Meta-Analysis of XRCC1 and its ability to interact with apurinic/ apyrimidinic endonuclease (Yan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that alterations in XRCC1 may play important roles in the process associated with the etiology of cancers because of the alteration of base excision repair functions (Monaco et al, 2007). The functional significance of XRCC1 Arg194Trp polymorphism is due to the location in an evolutionarily conserved region, and the occurrence of chromosomal breaks is largely increased among cases with the Arg/Arg genotype (Vodicka et al, 2007). The Arg280His is located in the PCNA-binding region of XRCC1, and could potentially alter the structure DOI:http://dx.doi.org/10.7314/APJCP.2012.13.12.6385 XRCC1 Genetic Polymorphisms and Thyroid Carcinoma Risk: a Meta-Analysis of XRCC1 and its ability to interact with apurinic/ apyrimidinic endonuclease (Yan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro data reported that cell lines bearing hOGG1 polymorphism, and therefore with a lower expression of hOGG1 protein, showed an increased radiosensitivity. 27,28 On the contrary, other studies highlighted that in case of radiation damage, Genetic polymorphisms predict response in rectal cancer E Cecchin et al the base excision repair does not always protect cells from biological consequences and a decreased hOGG1 expression level favors DNA repair efficacy after g-irradiation. The first step of base excision repair is catalyzed by the oxidative DNA glycosilase as hOGG1, which removes the altered purines or pyrimidines.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphic variants of OGG1, XRCC1, and APE1 genes have been reported to be responsible for functional changes at the protein level which may be related to cancer risk (Vodicka et al, 2007;Baute and Depicker, 2008), including nasopharyngeal carcinoma (Li et al, 2013), bladder cancer (Mittal et al, 2012), lung cancer (Osawa et al, 2010), esophageal cancer (Zhai et al, 2009), and cervical cancer (Li et al, 2012). Similarly, epidemiologic studies have examined the association between these inheritable BER pathway variations and the susceptibility to breast cancer; however, the results have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%